Strategi Dakwah Multikultural dan Perubahan Sosial di Purwokerto - Aris Saefulloh (Al-Ulum, 2021)
This article mainly aims to reveal the role of da'wah in social change, as well as how da'wah can be developed in a multicultural society. This study is a qualitative research, which aims to understand (to understand) social phenomena or a reality by focusing on a comprehensive description of the social phenomena being studied rather than breaking them down into interrelated variables. The results of the study show that da'wah is not just the delivery of messages of Islamic values, but also plays a role in the development of the times. Da'wah is able to encourage the productive power of the people or act as an agent of social change. Da'wah that can be developed in a multicultural society, among others: 1) da'wah is more oriented to aspects of quality than quantity, 2) da'wah is carried out on the concept of diversity, 3) da'wah with a local cultural and language approach, 4) continues to innovate da'wah, 5) understand the problems and needs of the people.